APPLICATION OF SEDIMENTARY ZEOLITE IN DAIRY CATTLE PRODUCTION - Lyubin N.A.; Dezhatkina S.V.; Akhmetova V.V.; Muchitov A.A.; Dezhatkin I.M.; Zyalalov S.R. (Russian Journal of Agricultural and Socio-Economic Sciences, 2020)
The study is aimed at studying the feasibility of using natural zeolites of sedimentary type as a feed additive to dairy cows. It was found that the inclusion of sedimentary zeolite in the diet of dairy cows improves the physiological and biochemical state of their body, increases metabolic processes, increases milk productivity by 12,9% ensures the production of environmentally friendly high-quality milk.